2021
DOI: 10.1007/s13555-020-00478-5
|View full text |Cite
|
Sign up to set email alerts
|

Lessons Learned from the First Decade of Laser-Assisted Drug Delivery

Abstract: Laser-assisted drug delivery augments the distribution and penetration of topically applied treatments, leading to enhanced delivery and bioavailability. We discuss the therapeutic application of laser-assisted drug delivery in clinical practice in cases of non-melanoma skin cancer, vitiligo, melasma, scarring, and alopecia (female pattern hair loss, male pattern hair loss, alopecia areata) as well as for vaccination, local anaesthesia, analgesia, viral warts, infantile haemangiomas and cosmetic uses, and we r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…[16] It has also been suggested that because of the barrier function of the stratum corneum, penetration of anesthetic into deeper skin layers is limited and pain relief is usually incomplete with surface anesthesia. [17] However, several studies have reported that laser treatment of keloid scars under surface anesthesia is mild and enough to achieve patient satisfaction. [18,19] The majority of patients in this study had tolerable pain, probably due to the adequate duration of surface anesthesia and the sealant package, which increased the temperature and hydration of the stratum corneum, and lidocaine cream is su ciently absorbed into the subcutis, blocking injurious transmission and achieving signi cant anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…[16] It has also been suggested that because of the barrier function of the stratum corneum, penetration of anesthetic into deeper skin layers is limited and pain relief is usually incomplete with surface anesthesia. [17] However, several studies have reported that laser treatment of keloid scars under surface anesthesia is mild and enough to achieve patient satisfaction. [18,19] The majority of patients in this study had tolerable pain, probably due to the adequate duration of surface anesthesia and the sealant package, which increased the temperature and hydration of the stratum corneum, and lidocaine cream is su ciently absorbed into the subcutis, blocking injurious transmission and achieving signi cant anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to CO 2 laser, Er:YAG laser has a much higher absorption coefficient of water in skin, leading to less energy to ablate tissues and subsequently minimal thermal damages around the microchannels ( Waibel et al, 2017 ). Since CO 2 laser creates deeper MTZs, it is therefore preferable to Er:YAG laser for topical drug delivery, although both methods are effective at providing therapeutic agents through the SC ( Searle et al, 2021 ).…”
Section: Physical Transdermal Drug Delivery Systemsmentioning
confidence: 99%
“…Laser treatment can selectively and precisely remove superficial skin in controlled and noncontact modes without the production of biohazardous waste [6]. Laser-assisted drug delivery has proven to be beneficial for treating melasma, actinic keratosis, skin cancers, vitiligo, and keloid scars in clinical practice [7,8].…”
Section: Introductionmentioning
confidence: 99%